PSYCHOLOGICAL TERRORISM AS A MEANS OF INFLUENCE ON SOCIETY AND PERSONAL CONSCIOUSNESS - Aleshchenko, Viktor; Khmiliar, Oleh (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . In today's realities, it is necessary to state the significant growth of terrorist movements, the globalization of the scale of their activities, as well as the high level of their organization and professionalism. Being identified with a weapon of mass destruction, which combines direct physical damage to victims with a significant psychological impact on society, psychological terrorism causes a purposeful destructive effect on the psyche of an individual. In this context, the urgent task of modern psychological science is the search for an optimal system of psychological protection and ensuring the information and psychological security of the individual and society against the effects of psychological terrorism. The purpose of the article is to reveal the essence of psychological terrorism as a form of non-lethal weapon and to develop the basic psychological principles of protection against its influence.M e t h o d s . The methodological basis of the scientific article consists of legal and systemic analysis, synthesis, interpretation method, comparison and hermeneutic method. Social transformations of members of religious sects are analyzed. R e s u l t s . It has been established that among the factors that determine the spread of psychological terrorism are the significant densification of the information environment, the increase in incompetence of the population in the conditions of hybrid warfare, the lack of proper information and psychological hygiene, the growth of marginality, the loss of social ties and alienation, the psychological illiteracy of the population as a prerequisite for any manipulations. All this often leads to the creation of a spiritual vacuum, which is filled with the "chaos of a new spirituality." Four main groups of sects operating in Ukraine have been identified. Among them: ceremonial, mystical, rationalist and totalitarian. The types of information-psychological, linguistic, psychotropic, psychophysical, somato-psychological weapons used by terrorists, exerting a psychological influence on individuals and society as a whole, are characterized.C o n c l u s i o n s . It has been proven that the problem of combating psychological terrorism requires an analysis of various crisis situations and the structure of terrorism itself as a phenomenon that has gone a long way of evolution from lone suicide bombers to huge terrorist organizations that commit acts of terrorism that entail the intimidation (death) of a large number of people. The conditions of high tolerance for attempts to engage in destructive cults are revealed, including: high social activity, high level of education, knowledge of foreign languages, access to various sources of information, various types of activities, professional career growth, vision of prospects for personal development.
Keywords: faith, religion, church, psychomanipulator, psychological terrorism, non-lethal weapons, psychological weapons